Discrepancies in national time trends of outpatient antibiotic utilization using different measures: a population-based study in France. (9th February 2018) - Trinh, Nhung T H; Chahwakilian, Pierre; Bruckner, Tim A; Sclison, Stéphane; Levy, Corinne; Chalumeau, Martin; Milic, Dejan; Cohen, Robert; Cohen, Jérémie F
Abstract: Objectives: To assess time trends of outpatient antibiotic utilization using different measures and explore their discrepancies. Methods: Based on French sales data from the IQVIA SDM database, 2009–16, we assessed time trends in outpatient antibiotic utilization using PrID, DID, PID and SID (defined as the number of prescriptions, DDDs, packages and standard units per 1000 inhabitants per day, respectively). We explored discrepancies between trends in PrID and DID by modelling the number of DDDs per prescription. Results: Outpatient antibiotic utilization ( n = 538.2 million projected prescriptions) decreased in terms of PrID, PID and SID (–10%, –8% and –8%, respectively; negative regression slopes; P < 0.01), but remained stable according to DID (+2%; slope 0.009; P = 0.4). The number of DDDs per prescription increased over time (+14%; slope 0.019; P < 0.001). The proportions of amoxicillin and amoxicillin/clavulanate were positively associated with the number of DDDs per prescription (adjusted coefficients 0.10 and 0.15, respectively; both P < 0.05), as well as the proportion of adult and hospital prescriptions (adjusted coefficients 0.07 and 0.05, respectively; both P < 0.05). The discrepancy between DID and PrID disappeared when the DDD of amoxicillin was increased to values higher than the current DDD. Conclusions: Time trends in outpatient antibiotic utilization expressed as PrID, DID, PID and SID provided conflicting results. We caution against using DID alone when monitoring antibiotic utilization. Instead, we recommend monitoring both DID and PrID as they provide different types of relevant information, especially when studying trends at a national level.